Medium-term cycles and housing: Is regional integration different?. (July 2019) - Gray, David
Drehmann et al. (Drehmann M, Borio C and Tsatsaronis K (2012) Characterising the financial cycle: Don't lose sight of the medium term! BIS Working Papers, No. 380. Bank for International Settlements, June) of the BIS lament the attention given to medium-term cycles. They highlight a financial cycle characterised by longer cycles in credit and property prices. Although the co-movement of regional residential property prices has been well-explored, they have not been examined in this range. For the UK what is found is that, despite the ripple effect being more evident at the medium-term cycles, the degree of integration is greater than in the business range. Moreover, the segmentation of the UK is related to arcs. An Outer South, which surrounds London, is topped by the Midlands, with a less well integrated Northern grouping. Not only does this appear to reflect a monocentric system, but it also implies that price cycles and price leadership could be related to price levels . With differing price levels as a proxy for sensitivity to financial fluctuations, finance appears to be promoting both housing market integration and, with London, dissimilarity. Drehmann et al.'s call for the medium-term cycles to be made a policy focus is endorsed, but with the proviso that a London-centric view of the impact of credit liberalisation is important for national cohesion.